2020
DOI: 10.1002/ppul.24699
|View full text |Cite
|
Sign up to set email alerts
|

Viral strategies predisposing to respiratory bacterial superinfections

Abstract: Acute respiratory infections are amongst the leading causes of childhood morbidity and mortality globally. Viruses are the predominant cause of such infections, but mixed etiologies with bacteria has for decades raised the question of the interplay between them in causality and determination of the outcome of such infections. In this review, we examine recent microbiological, biochemical, and immunological advances that contribute to elucidating the mechanisms by which infections by specific viruses enable bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 107 publications
(311 reference statements)
1
50
0
4
Order By: Relevance
“…Vitamin D helps maintain tight junctions, gap junctions, and adherens junctions (e.g., by E-cadherin) [18]. Several articles discussed how viruses disturb junction integrity, increasing infection by the virus and other microorganisms [19][20][21].…”
Section: Vitamin D and Mechanisms To Reduce Microbial Infectionsmentioning
confidence: 99%
“…Vitamin D helps maintain tight junctions, gap junctions, and adherens junctions (e.g., by E-cadherin) [18]. Several articles discussed how viruses disturb junction integrity, increasing infection by the virus and other microorganisms [19][20][21].…”
Section: Vitamin D and Mechanisms To Reduce Microbial Infectionsmentioning
confidence: 99%
“…Vitamin D functioning of immune system helps maintain tight junctions, gap junctions, and adherens junctions. Viral disease affects the junction integrity thereby increasing the rate of infections in the host (Rossi et al 2020 ). Deficiency of vitamin D may reduce 25-hydroxyvitamin D (25OHD) levels thereby affecting the host.…”
Section: Role Of Vitamin D To Fight Against Viral Infectionsmentioning
confidence: 99%
“…Furthermore, HCQ seems to inhibit important functional proteins for COVID-19 replication, with potency increasing in the series PLpro, 3CLpro, RdRp [ 21 ]. It has been reported that supplements with vitamin A, B, C, D, and E seems to have a beneficial effects in patients with viral infections as COVID-19 [ 2 , 22 – 25 ]. Within such a panorama, it is worth mentioning that vitamin D mitigates the scope of acquired immunity and regenerates the endothelial lining.…”
Section: Introductionmentioning
confidence: 99%